Chapter Slow Violence and Slow Going Encountering Beckett in the Time of Climate Catastrophe - Salisbury, Laura (Springer Nature, 2023)
This This chapter reads Beckett's fascination with what Steven Connor has called 'slow going' alongside Rob Nixon's description of the 'slow violence' of climate breakdown. Following Nixon's suggestion that 'slow violence' does not register readily in narratives and temporalities of crisis, I examine Beckett's attention to what remains in a paradoxically stuck and ongoing time. Suggesting that Beckett's work sticks with and witnesses catastrophe rather than crisis, the chapter uses The Lost Ones to explore Beckett's commitment to staying with a disaster that cannot be overcome, alongside the articulation of a giving up that is not a decision but part of a drive to go on. Using Beckett's interest in Freud's death drive, I suggest that Beckett's later texts work through materialisations of attachment and dependence as a way of thinking with and living with, rather than denying or repressing, the reality of the 'nothing to be done'.